Micro-economic study of earnings in Ireland - Walsh, B.M.; Whelan, B.J. (Economic & Social Studies, 1976)
This article, which is a first attempt to analyse Irish earnings data at the level of the individual, is based on a human capital approach. It shows that about half the variance in individuals' earnings can be accounted for by their age, education, occupation, urban/ rural residence, trade union membership, marital status and state of health. It also demonstrates the divergence between male and female earnings, and examines some of the factors underlying this divergence. Returns to education and training are derived and returns to males are shown to be considerably above those to females.
Keywords: Economics; Sociology